B Cell–Activating Factor Promotes B Cell Survival in Ectopic Lymphoid Tissues in Nasal Polyps - Wang, Zhe-Zheng; Song, Jia; Wang, Hai; Li, Jing-Xian; Xiao, Qiao; Yu, Ze; Liu, Jin-Xin; Liu, Zheng (Frontiers in Immunology, 2021)
Ectopic lymphoid tissues (eLTs) characterized by B cell aggregation contribute to the local immunoglobulin production in nasal polyps (NPs). B cell-activating factor (BAFF) is vital for B cell survival, proliferation, and maturation. The purpose of this study is to investigate whether BAFF is involved in the B cell survival and eLT formation in NPs. The mRNA and protein levels of BAFF in NP tissues with and without eLTs were detected by PCR and ELISA assay, respectively. The cellular sources of BAFF and active caspase-3-positive B cells in NPs were studied by immunofluorescence staining. B cells purified from NP tissues were stimulated with BAFF and were analyzed by flow cytometry. Stromal cells purified from NP tissues were stimulated with lymphotoxin (LT) α1β2, and BAFF levels in culture supernatants were analyzed by ELISA. Compared with those in control tissues and NPs without eLTs, the BAFF levels were elevated in NPs with eLTs. Abundant BAFF-positive cells and few active caspase-3-positive apoptotic B cells were found in NPs with eLTs, in contrast to those in NPs without eLTs. There was a negative correlation between the numbers of BAFF-positive cells and frequencies of apoptotic B cells in total B cells in NP tissues. BAFF protected nasal polyp B cells from apoptosis in vitro. Stromal cells were an important cellular source of BAFF in NPs with eLTs. LTα1β2 induced BAFF production from nasal stromal cells in vitro. We propose that BAFF contribute to eLT formation in NPs by promoting B cell survival.